Acute Closed Angle Glaucoma : A Case Report - Cyntia Mago, Helen (Indonesian Health Journal, 2023)
Glaucoma is an eye disorder characterized by disruption of the tissue and integrity of eye function. This study aims to describe a case of Glaucoma along with an explanation and management of its therapy so that it can help increase knowledge and detect it early. This type of research is a descriptive case study. The research was conducted at an eye clinic on February 12 2022 on patients who were diagnosed with acute angle closure glaucoma through anamnesis and direct physical examination of the patient. Based on the results of the anamnesis and physical examination obtained, Mrs. K was diagnosed with acute left angle closure glaucoma, an eye disorder that occurs due to a rapid increase in intraocular pressure as a sign of anterior eye closure. room, blocking the flow of aqueous humor. In this case, Timolol maleate 0.5% ED 2 dd gtt 1 OS therapy was given, a beta (?)-adrenergic receptor antagonist whose function is to reduce aqueous humor production. Apart from that, Acetazolamide 250 mg 3x1 therapy was also given, which is a class of carbonic anhydrase inhibitor which functions to suppress the production of aqueous humor. The conclusion of this study is that the most common cause of glaucoma is obstruction of aqueous humor outflow due to pupillary blockade, closure of the angle of the anterior chamber, narrowing of the trabecular meshwork and increased episcleral venous pressure thereby increasing intraocular pressure.